Characteristics of Hybrid Pla and Carbon-Pla in Different Laminates Formations - Muhammad Ibnu Rashyid; Ardi Wiranata; Muhammad Akhsin Muflikhun (Journal of Fibers and Polymer Composites, 2023)
The multi-extruder printer allows to printing of different materials into one product. This paper experimented on multi-material lamination using PLA with rigid characteristics and Carbon-PLA with elastic characteristics. The flexural and shore hardness test was chosen to understand how two different materials affect each other. The results show that the different lamination performances affect the flexural strength. The highest flexural strength from 3 laminations was the CPC of 53.33 MPa, this is 3.03% lower than the PLA only and 37.9% higher than Carbon-PLA only. From the 2 laminate specimens the PC laminates achieved the highest flexural strength of 73.07 MPa, the value is 5.4% higher than the PLA only and 50.01% higher than Carbon-PLA only. The shore hardness value showed no significant changes between the lamination and 1 material only. It was also proved that lamination formation can increase the flexural strength or lead to detrimental results. This finding enables the designer of multi-material 3D printing to consider the formation of materials.